Sharia Leasing Transaction System in the Financial Industry - Fahmi Alif Aldianto; Pera Wibowo Putro; Neni Utami; Yuni Rinawati (JOURNAL OF SHARIA ECONOMICS, 2023)
The sharia leasing system applies to all financing carried out and innovated according to sharia principles dan in line with concepts in sharia principles. In addition, this system still has weaknesses: high capital investment does not prevent those who carry out these activities from breaking their promises. Therefore, regulations are needed that regulate more precisely to minimize this. This study uses a critical analytical review method based on a literature review using data from journals, books and information from the internet. The results of the analysis show that contract-based financing companies that finance the company's operations are in accordance with sharia principles. Sharia leasing can apply the principles of efficiency, innovation, and compliance with sharia norms.